Diego Martínez Torrón (ed.), Sobre Cervantes. Centro de Estudios Cervantinos, Alcalá de Henares, 2003; 272 pp. - Rodríguez, Adriana Azucena (El Colegio de México, 2005)
Se reseñó el libro: Sobre Cervantes.